2012
DOI: 10.1108/02651331211201543
|View full text |Cite
|
Sign up to set email alerts
|

A contingency approach to international marketing strategy and decision‐making structure among exporting firms

Abstract: Purpose-Although the relation between standardization/adaptation strategy and performance has been extensively examined in the international marketing literature, the findings concerning these factors are still inconclusive. The conflicting results might relate to the analysis approach adopted in prior research, which tends to focus on the direct effect of marketing strategies. By utilizing the contingency theory, the purpose of this paper is to uncover the moderation factors for the strategystructure-performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 67 publications
2
79
0
2
Order By: Relevance
“…-Influences the effectiveness of strategies employed (Global/Glocal/Regcal/Local) for channel decisions (Chung, Wang, and Huang 2012). -Low levels help to increase trust (Armstrong and Yee 2001;Bianchi and Saleh 2010).…”
Section: Psychic Distancementioning
confidence: 99%
“…-Influences the effectiveness of strategies employed (Global/Glocal/Regcal/Local) for channel decisions (Chung, Wang, and Huang 2012). -Low levels help to increase trust (Armstrong and Yee 2001;Bianchi and Saleh 2010).…”
Section: Psychic Distancementioning
confidence: 99%
“…Environmental turbulence is considered impact SMEs; therefore, it becomes necessary for SMEs to use a careful combination of contingency variables and decision-making structure to obtain optimal performance (Chung et al, 2012). Environmental turbulence refers to a business environmental feature regarding the customers and their preferences for new products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The core of a business's projected image is its brand identity, which is reflected by its adopted name, logo, colour, slogan and typography (Melewar & Saunders, 1998). The decisions towards the adoption of branding standardization/adaptation strategies have stimulated considerable interest among academics and others with regard to the formulation of appropriate international marketing strategies (Cavusgil & Zou, 1994;Chung, Lu Wang & Huang, 2012;Demetris et al, 2009;Jain, 1989;Okazaki, Taylor & Zou, 2006;Theodosiou & Leonidou, 2003). For example, Rosson and Brooks' (2004) study found that, in 80% of cases, the targets assumed the acquirers' brand identities.…”
Section: Introductionmentioning
confidence: 99%